Viability of Various Sources to Ignite A2L Refrigerants - Dennis K. Kim; Peter B. Sunderland (Energies, 2020)
Environmental considerations are motivating the adoption of low global warming potential refrigerants. Most of these are mildly flammable, i.e., A2L. Their susceptibility to ignition from various ignition sources is poorly understood, particularly for the stoichiometric and quiescent mixtures that are emphasized here. The viability of fifteen residential ignition sources to ignite four A2L refrigerants is considered. Tests are performed in a windowed chamber with a volume of 26 L. The refrigerants are R-32 (difluoromethane); R-452B (67% R-32, 26% R-1234yf, and 7% pentafluoroethane); R-1234yf (2,3,3,3-tetrafluoropropene); and R-1234ze (1,3,3,3-tetrafluoropropene). Two types of ignition sources are confirmed here to be viable: a resistively heated wire at 740 °C and open flames. When the refrigerant concentration was increased slowly, candle flames and butane flames extinguished before initiating any large deflagrations. Eleven other sources were not viable: a smoldering cigarette, a butane lighter, friction sparks, a plug and receptacle, a light switch, a hand mixer, a cordless drill, a bread toaster, a hair dryer, a hot plate, and a space heater. The difficulty to ignite these refrigerants in air is attributed to their long quenching distances (up to 25 mm). Under some conditions the refrigerants were observed to act as flame suppressants.